2023
DOI: 10.3390/nu15071779
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Gut Microbiome and Serum Metabolome in Patients with Functional Constipation

Abstract: Functional constipation (FC) is a gastrointestinal disorder with high incidence, and it seriously affects patients’ physical and mental health. Several studies have shown that the gut microbiome is associated with FC, but these studies have produced inconsistent findings, with few reflecting the relationship between the gut microbiome and metabolites. This study used 16S rRNA microbial genomics and non-target metabolome based on liquid chromatography–mass spectrometry to analyze the gut microbiota composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Gastrointestinal dysbiosis plays a significant role in the pathogenesis of FC. Some studies have shown that patients with FC have significant differences in their intestinal microbiota compared to healthy individuals ( 44 , 45 ). Moreover, some studies have found the changing of certain microbial groups in older people ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal dysbiosis plays a significant role in the pathogenesis of FC. Some studies have shown that patients with FC have significant differences in their intestinal microbiota compared to healthy individuals ( 44 , 45 ). Moreover, some studies have found the changing of certain microbial groups in older people ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oligosaccharides, konjac glucomannan, and yellow tea extracts all significantly reduced the abundance of Bacteroides in animals with constipation (Wang et al, 2017;Hayeeawaema et al, 2020;Cao et al, 2021). The results of clinical studies have also shown that FC patients have a higher abundance of Bacteroides, especially elderly FC patients (Guo et al, 2020;Wang et al, 2023). A study evaluating the safety and efficacy of fecal microbiota transplantation for chronic FC suggested that a high abundance of Bacteroides may be one of the causes of constipation (Tian et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports that the concentration level of Bacteroides decreases with age [17], so the median age of the participants should be close in order to compare the findings of other research groups. Moreover, the concentration levels of different genera could be influenced by diarrhea and constipation and these should be considered when including patients in a study [71,72]. For example, it has been reported that patients with functional constipation had higher levels of Bacteroides [71] and that other comorbidities, such as gall stones, could alter the composition of the microbiome [72].…”
Section: Discussionmentioning
confidence: 99%